A novel device for the clinical assessment of intranasal trigeminal sensitivity - Naka, Asami; Wolf, Axel; Renner, Bertold; Mueller, Christian A. (Annals of Otology Rhinology and Laryngology, 2014)
Despite the significance of trigeminal pathology, practical clinical tests that accurately evaluate intranasal trigeminal function are scarce. The aim of the present study is to introduce a practical procedure for the assessment of intranasal trigeminal sensitivity.We developed a device to stimulate the nasal mucosa using carbon dioxide, which is self-administered intranasally by holding down a timed button until the required sensory response has been triggered. The trigeminal sensitivity is derived from the measured administration time in conjunction with the concentration of carbon dioxide administered. Sixty-three healthy participants were used to validate the device, after which the new device was compared with a standard lateralization task in an additional 16 participants. In 20 participants, the experiment was repeated to verify test-retest reliability.Statistical analysis showed significant consistency in administration-duration in healthy individuals, including those in the test-retest group. Those participants with higher scores in the lateralization task were found to show higher intranasal sensitivity measured by the new device.Herein, we present the design and validation of a novel device for the practical assessment of intranasal trigeminal sensitivity. In this study, we demonstrate the efficacy and reliability of this device.
EVALuna2:8520